Does sugarcane vinasse composition variability affect the bioenergy yield in anaerobic systems? A dual kinetic-energetic assessment. (10th December 2019) - Santos, Priscilla Soares; Zaiat, Marcelo; Oller do Nascimento, Claudio Augusto; Fuess, Lucas Tadeu
Abstract: The anaerobic processing of sugarcane vinasse has been recently highlighted as an effective approach to both mitigate negative impacts of its inadequate management and recover renewable energy through biogas production. However, basic aspects of the process still require further investigations, such as understanding the impacts of the compositional variability of vinasse on the overall performance of anaerobic systems. In this context, the impacts of different types of sugarcane vinasse, i.e., from annexed (VinAn) and autonomous (VinAu) ethanol plants and spirit production (VinAl), on methane production and organic matter removal were assessed under mesophilic conditions (37 °C) from a kinetic perspective. The energetic potential of the biogas was also investigated regarding micro (methane yield) and macro (contributions to the Brazilian energy matrix) scales. The availability of biodegradable organic matter and sulfate had a direct impact on the kinetics of methane production, associating a 2-fold higher initial methane production rate with VinAl (10.12 NmL h −1 ) compared to VinAn (5.95 NmL h −1 ) and VinAu (4.25 NmL h −1 ). However, the methane yield was not affected by the compositional variations (328–339 NmL-CH4 g −1 COD), which indicates that vinasse may be efficiently used as substrate for bioenergy generation, regardless of its origin. The global energy production estimated for VinAn (24, 816 GWh) was over 6- and 7-fold higher compared to VinAu (3984 GWh) and VinAl (3035 GWh) due to discrepancies in vinasse generation flow rates, potentially increasing the available renewable power supply in Brazil by 2.2% or over 1400% of the current bioenergy produced from biogas. Overall the electric energetic potential of sugarcane vinasses (14, 486 GWh) could replace over 20% of natural gas or 90% of coal use in Brazil, satisfactorily decreasing the dependence on non-renewable energy sources. Graphical abstract: Image 1 Highlights: Bioenergy recovery from different types of sugarcane vinasse was investigated. The availability of organic matter and sulfate directly impacts process kinetics. Compositional variations do not impact the methane yield. Vinasse from annexed ethanol plants presented the highest global energy potential. Energy from biogas could replace 90% of the coal-derived energy in Brazil.